Pelaksanaan Kebijakan Vaksinasi Covid-19 oleh Badan Permusyawaratan Desa (BPD) di Desa Sumbersekar Kabupaten Malang - Adhinda Dewi Agustine; Marliana Eka Fauzia; Yogi Hertanto; Caesar Demas Edwinarta (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2022)
Since the outbreak of the Covid-19 case in Indonesia at the end of 2019 and its ever-increasing spread, the government has aggressively taken all forms of efforts to tackle the COVID-19 case, especially by promoting vaccination programs at all levels of society, especially villages. The existence of the Village Consultative Body (BPD) in carrying out vaccinations in Sumbersekar Village also provided socialization about the importance of social restrictions, implementing rules for wearing masks, washing hands with soap, maintaining distance, and carrying out complete vaccinations for all people in the village as a form of resistance or prevention. against covid-19. The Village Consultative Body (BPD) is assisted by village officials, community leaders also supervise, coordinate the implementation of vaccination activities carried out and provide education or direction to the community that the vaccination is not dangerous. The amount of news in the mass media also has an influence on the public regarding the increase in cases of COVID-19 and vaccinations carried out so that many people are afraid to vaccinate.